Acidity of Rain and Fog: Conceptual Definitions and Practical Measurements of Acidity - Carola Annette Johnson; Laura Sigg (CHIMIA)
Conceptual definitions are applied to the measurement of acidity and pH. A reliable method is described, and the use of Gran plot titrations as a diagnostic tool in rainwater and fogwater analysis is shown.